Theoretical study of the spectroscopic properties of mendelevium (Z=101). (May 2020) - Li, Jiguang; Dzuba, Vladimir
Highlights: Using recently developed version of the configuration interaction method for atoms with open shells we calculate electron structure and spectroscopic properties of the mendelevium atom (Md, Z = 101 ). These include energy levels, first and second ionisation potentials, electron affinities, hyperfine structure and electric dipole transition amplitudes between ground and low lying states of opposite parity. The accuracy of the calculations is controlled by performing similar calculations for lighter homolog of mendelevium, the thulium atom and comparing the results with experiments and other calculations. The calculations for Md are to address the lack of experimental data and help in planing and interpreting the measurements. It is the first time to report two possible energy levels bound states 5f 13 7s 2 7p 5 F3 and 5f 13 7s 2 7p 3 G4 for the negative ion of Md, and the electron affinity was predicted to be  ∼ 0.169 eV. Abstract: Using recently developed version of the configuration interaction method for atoms with open shells we calculate the spectroscopic properties of the mendelevium atom (Md, Z = 101 ). These include energy levels, first and second ionisation potentials, electron affinities, hyperfine structure and electric dipole transition amplitudes between ground and low lying states of opposite parity. The accuracy of the calculations is controlled by performing similar calculations for a lighter homolog of mendelevium, the thulium atom and comparing the results with experiments and other calculations. The calculations for Md are to address the lack of experimental data and help in planning and interpreting the measurements.